Conducting and utilizing evaluation for multiple accountabilities: A study of nonprofit evaluation capacities. Issue 3 (18th August 2020) - Bryan, Tara Kolar; Robichau, Robbie Waters; L'Esperance, Gabrielle E.
Abstract: This article combines the evaluation capacity building and nonprofit accountability literature to examine how nonprofits use evaluation data to address stakeholder expectations. Our study investigates how staff competency, technological resources, learning climate, and strategic planning influence a nonprofit's ability to demonstrate upward, lateral, and downward accountabilities. Results indicate different combinations of evaluation capacities matter more for particular stakeholder groups. We argue a more integrative nonprofit accountability requires that managers and staff know how to utilize evaluation results for internal and external audiences. Nuances between specific evaluative capacities and their influences on multiple accountabilities suggest several implications for practice.